Some instability puzzles in Kaleckian models of growth and distribution: A critical survey - Eckhard Hein; Marc Lavoie; Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2008)
We tackle the issue of the possible instability of the Kaleckian distribution and growth model and the consequences for the endogeneity of the equilibrium rate of capacity utilization and for the paradox of thrift and the paradox of costs. Distinguishing between Keynesian and Harrodian instability, we review various mechanisms that have been proposed to tame Harrodian instability while bringing back the rate of utilization to its normal rate. We find that the mechanisms that have been suggested are far from being convincing. We thus review some approaches arguing that the adjustment towards a predetermined normal rate should not be expected at all, either because the normal rate reacts to the actual rate, or because of other constraints on the behaviour of entrepreneurs. We conclude that Kaleckian models are more flexible than their Harrodian and Marxian critics suppose when attacking the simple textbook version.
urn:nbn:de:101:1-2009031829
Keywords: E12; E20; O41; 330; Kaleckian models; distribution; investment function; stability; utilization rate.